Compensação das formas de onda distorcidas pela saturação de transformadores de corrente com auxílio da estimação de frequência - Santos, Eduardo Machado dos (2015)
This work presents innovative methods for detection and correction of the distorted portions of the secondary current waveforms, which occur due to the core saturation of current transformers (CTs). The detection technique is based on the analysis of the plans formed by the secondary current (i2) and their difference-functions (deln). The distance between consecutive points in these plans has a significant increase when saturation occurs, bucking the trend during the undistorted intervals, which are not corrupted by CT saturation. Additionally, the proposed correction of these signals is based on a technique of curve fitting by least squares, which uses the frequency signal estimated from the secondary current signals as a parameter of compensation. The aforementioned frequency signal is estimated using the Mathematical Morphology operators of dilation and erosion, which are used to estimate future values of the α and β signals obtained from the Clarke Transform. Computational simulations of short circuits were performed to obtain the secondary current signals distorted by CT saturation. The detection method was evaluated in terms of the ability to identify saturation intervals and its speed of response. Moreover, the correction technique was evaluated in terms of the compensation accuracy and its processing time. Calculations of transient error and the use of a full cycle Fourier filter were the basis for the qualitative analysis of the performance of the correction technique. The tests revealed that the combination of the proposed techniques ensures excellent accuracy during correction signals distorted by saturation, showing that the proposals constitute a robust tool for use in numerical relays, increasing the reliability of protection schemes in situations involving the saturation of TCs.